Kajian Tata Udara Ruang Bersih Kelas B pada Pembuatan Obat Diabetes - Susilawati, Susilawati; Setiawan, Andriyanto; Rohayani, Diah; Rachmawati, Putri (Universitas Muhammadiyah Yogyakarta, 2020)
Clean room is a room with the amount of air deposition controlled, classified, designed, constructed and operated by controlling particles in the air. And the parameters that are controlled such as temperature, relative humidity, debit and number of particles. The drug manufacturing process must meet CPOB (Cara Pembuatan Obat yang Baik) standards in order to obtain quality drugs. The purpose of knowing the critical factors of the clean room in terms of air conditioning, namely temperature and Relative Humidity (RH), looking at air flow, air exchange, seeing the return discharge with air recirculation quality and seeing the number of particles in accordance with CPOB, the research method was carried out by taking data on a drug company, PT. X in Bandung and literature study to compare with the prevailing CPOB standards. The results of the study show that the critical factor is the measured air temperature of 17-22oC with RH 45-57% and meets CPOB standards, namely temperatures of 16-25oC with RH 45-55%. The rated air supply discharge is 5,000 m3 / hour with air exchange / ACH (Air Change Hour), meeting the average standard of 118.5 times per hour. Meanwhile, the measured return discharge is 750-2000 m3 / hour and is well recirculated. The number of particles for the size of 0.5 Âµm and 5 Âµm was 38,081 and 46 particles met the CPOB standard because the maximum standard was 325,000 and 2,900 particles.